Wish girl - Loftin, Nikki (Razorbill, a division of Penguin Young Readers Group, 2015)
Twelve-year-old Peter has never felt at home with his noisy family, but begins to find the strength to live and to be himself when he discovers a special valley in the Texas Hill Country and meets Annie, a girl dying of cancer who knows and accepts him from the start.